1974
DOI: 10.1136/bmj.1.5907.549
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and Serotonin Metabolism in Hepatic Encephalopathy

Abstract: SummaryPatients with stupor or coma from fulminant hepatic failure were found to have high cerebrospinal fluid concentrations of homovanillic acid (HVA) and 5-hydroxyindole acetic acid (5-HIAA), metabolites of dopamine and serotonin respectively. Excessive amounts of their precursors-phenylalanine and tyrosine and free tryptophan -were found in the patients' plasma. Methionine, which participates in dopamine degradation, was also much increased. Similar disturbances were found in patients suffering an acute ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

1975
1975
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(30 citation statements)
references
References 18 publications
(7 reference statements)
2
27
0
1
Order By: Relevance
“…No significant differences were found in the values of plasma total tryptophan, free tryptophan and f-Trp/t-Trp ratio in patients with liver cirrhosis, liver cirrhosis + hepatocellular carcinoma, hepatocellular carcinoma and liver cirrhosis with encephalopathy but no bleeding tendency compared with healthy controls. There are reports that plasma free tryptophan is significantly higher in liver cirrhosis (28), or hepatic encephalopathy of liver cirrhosis than in healthy controls (19,(29)(30)(31). These values were obtained, however, by measuring the tryptophan concentration in the filtrate after centrifugation without pH control, and without Separation of tryptophan from other amino acids and components related to tryptophan which might influence the fluorescence assay of tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…No significant differences were found in the values of plasma total tryptophan, free tryptophan and f-Trp/t-Trp ratio in patients with liver cirrhosis, liver cirrhosis + hepatocellular carcinoma, hepatocellular carcinoma and liver cirrhosis with encephalopathy but no bleeding tendency compared with healthy controls. There are reports that plasma free tryptophan is significantly higher in liver cirrhosis (28), or hepatic encephalopathy of liver cirrhosis than in healthy controls (19,(29)(30)(31). These values were obtained, however, by measuring the tryptophan concentration in the filtrate after centrifugation without pH control, and without Separation of tryptophan from other amino acids and components related to tryptophan which might influence the fluorescence assay of tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been shown that Trp usually occurs as bound to serum albumin in the circulation and the free Trp fraction in serum increases in patients with liver diseases, probably due to elevated free fatty acids and hypoalbuminemia (Ono et al 1978;Yoshida and Hirayama 1980). There are conflicting reports, however, that no consistent relationship could be observed between the plasma Trp level and increase of serotonin or its metabolites in the cerebrospinal fluid in patients with hepatic coma (Knell et al 1974;Lal et al 1975.). Thus the relationship of Trp and its metabolites to hepatic encephalopathy remains to be clarified.…”
mentioning
confidence: 91%
“…L-Dopa, Bupropion oder Kokain, delirante Zustände auslösen können [52,53]. Ebenfalls dürfte ein Dopaminüberschuss die Ursache für die Entwicklung deliranter Zustände im Rahmen einer hepatischen Enzephalopathie sein [54]. Andererseits sind klassische Neuroleptika, wie z.B.…”
unclassified